The Impact of HbA1c level on heart failure with recovered rjection fraction in patients with Type 2 Diabetes. (14th October 2021) - Yang, C.D; Wang, X.Q
Abstract: Background: Heart failure (HF) with improved or recovered ejection fraction (EF, HFrecEF) has been recognized as a new type of HF with different underlying clinical phenotype, pathophysiology and prognosis. However, few studies have analyzed the relationship between type 2 diabetes and HFrecEF, and the impact of glycemic level on myocardial function recovery. Purpose: In the present study, we sought to investigate the relation between HbA1c level and HFrecEF in patients with type 2 diabetes. Methods: A total of 796 HF patients with reduced left-ventricular ejection fraction (LVEF, <40%) and type 2 diabetes were consecutively enrolled from August 2012 to July 2020. During follow-up for up to 24 months, patients were classified into HFrecEF for whom developed recovered LVEF (≥40% and absolute increase ≥5%) and HFrEF for whose LVEF was persistently reduced (<40%). The relation between HbA1c and the recovery of LV function was analyzed. Results: HF patients with type 2 diabetes had significantly lower rates of LVEF recovery when having higher versus lower HbA1c levels in the baseline (the lowest tertile: 62.4%, intermediate tertile: 50.4%, the highest tertile: 46.8%; P<0.001). There were stepwise decreases in changes of LVEF (P<0.001) and increases in changes of LV end-systolic diameter (LVESD; P=0.093) with increasing tertiles of LVEF during follow-up. In the subgroup analysis, the impact of HbA1c on LVEF recovery was more prominent in patients with ischemic heart disease (P<0.001) than those with dilated cardiomyopathy (P=0.536). A significant interaction term was present between HbA1c and etiology of heart failure with regard to LVEF recovery (P=0.012). After multivariate adjustment of conventional confounding factors, high HbA1c level remained to be an independent risk factor lower incidence of HFrecEF in patients type 2 diabetes. Conclusions: Our study suggests that optimal glycemic control is an independent predictor for incidence of HFrecEF in patients with type 2 diabetes. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Natural Science Foundation of China, Shanghai Municipal Commission of Health and Family Planning